Recognition of Metal Objects inside Wall using Antipodal Vivaldi Antenna - Faraz Ahmed Shaikh; Sheroz Khan; Zarimin Zaharudin; AHM Zahirul Alam; Farah Diyana Bt. Abdul Rahman; Khairayu Bt. Badron; Dominique Baillargeat; Mashkuri Bin Yaacob; Zeeshan Shahid (Institute of Advanced Engineering and Science, 2018)
This paper present a recognition technique of metal placed inside and between two walls. A unique scheme of recognition of metallic objects through Ultra Wide Band (UWB) Modified Antipodal Vivaldi Antenna (MAVA) frequency range of (3.1GHz to 10.6 GHz) is presented in this paper.The working mechanism of detection system based on Time Domain Reflectrometry (TDR) using through wall imaging (TWMI). A very small duration pulses generated by Vector Network Analyzer (VNA) which are used for illuminate the wall.The analysis of a system under UWB antenna probe array. The simulation results of MAVA have given an enormous potential of penetration, in order to recognize concealed metal objects with fine precision, proving a smart development in the detection system technology. The improvement of resolution in an image, special filters have been developed and implemented. The design and optimization progression is conceded out via CST simulation software for parametric performance assessment of return loss, radiation pattern and directivity.